Reconciling Drivers of Seasonal Terminus Advance and Retreat at 13 Central West Greenland Tidewater Glaciers. Issue 7 (31st July 2018) - Fried, M. J.; Catania, G. A.; Stearns, L. A.; Sutherland, D. A.; Bartholomaus, T. C.; Shroyer, E.; Nash, J.
Abstract: The majority of Greenland tidewater glaciers undergo a seasonal cycle in terminus position, characterized by wintertime advance and summertime retreat. Understanding mechanisms that control seasonal cycles can help elucidate how tidewater glaciers regulate dynamic ice loss on longer timescales. However, controls on terminus position are numerous and complex. To address this, we compare time series of satellite‐derived terminus positions for tidewater glaciers in central west Greenland with observations of environmental forcings, including runoff at the grounding line, mélange presence, and, where available, ocean temperature in the proglacial fjord. We show that for most glaciers, seasonal terminus positions are more sensitive to glacial runoff than mélange or ocean thermal forcing. The strength of this relationship differs for two end‐member glacier types in the region, defined by their terminus geometry and dominant calving style. First, we find a strong relationship between magnitudes of runoff and terminus retreat at tidewater glaciers with shallow grounding lines (<400 m) that calve primarily through small‐magnitude serac failures. At these glaciers, subglacial plumes drive submarine melt and locally enhance retreat, causing heterogeneous position change across the terminus and local embayments where seasonal terminus changes are largest. In contrast, deep termini susceptible to buoyant flexure retreat sporadically through full ice thickness calving events less dependent on runoff. While less common, these glaciers deliver larger ice fluxes to the ocean. With predicted surface melt increases and diminished mélange coverage in a warming climate, our results reveal the impact of environmental forcings on diverse tidewater glacier systems in the region. Plain Language Summary: Terminus position changes at tidewater (marine‐terminating) glaciers are largely responsible for patterns of mass loss from the Greenland ice sheet. However, we lack constraints on mechanisms that control Greenland tidewater glacier terminus positions through time. To address this, we compared records of seasonal terminus positions derived from satellite imagery to potential forcing mechanisms including meltwater runoff, mélange, and ocean temperatures for 13 glaciers in central west Greenland. We find that most glacier termini in the region correspond closely to runoff variability. This relationship is strongest at glaciers with shallow grounding lines that undergo small‐magnitude calving events and where runoff‐driven subglacial melt plumes drive terminus retreat. In contrast, deep termini that experience large, sporadic calving events appear less sensitive to runoff and submarine melting. Key Points: We evaluate the correlation of seasonal terminus advance/retreat to glacial runoff, ice mélange, and ocean temperature Runoff is the strongest predictor at glaciers that calve via serac failures where subglacial melt plumes locally enhance retreat Glaciers with sporadic, buoyancy‐induced full‐thickness calving and the largest ice fluxes are less sensitive to environmental forcings